Preparation method of high-purity nano colloidal silica oxide
High-purity nano-oxide silica gel prepared by using equipment made of specific materials and organic silane hydrolysis method, the problem of metal ion contamination during the CMP process is solved, and efficient polishing effect and high yield products are achieved.
Patent Information
- Application Number
- CN202411825730.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
During the chemical mechanical polishing (CMP), it is difficult for the prior art to effectively eliminate metal ion contamination, resulting in chip leakage, short circuit and other problems, affecting the product yield, and poor polishing effect, low material removal rate, and rough wafer surface.
High-purity nano-silica colloids are prepared by using equipment and pipelines made of polyethylene PE, polypropylene PP, polytetrafluoroethylene PTFE, soluble polytetrafluoroethylene PFA and other materials to ensure that no metal ions are introduced during the CMP process. Nano-silica particles are prepared by organic silane hydrolysis method to improve the uniformity of the particle size distribution.
It effectively reduces the probability of metal ion contamination during CMP, improves the material removal rate and polishing effect, reduces wafer surface scratches, and improves product yield and production efficiency.
Smart Images

Figure CN119797374A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing high-purity nano silica colloidal solids, belonging to the field of fine chemicals. Background Art
[0002] With the development of semiconductor processing technology, the size of very large-scale integrated circuits has been reduced, and more components can be manufactured on the surface of a silicon wafer of the same size, which means that the density of components and metal connections on the wafer surface needs to be increased. In the wafer processing technology, the wafer needs to be globally flattened before the subsequent photolithography and deposition processes can be carried out; and after the new material is deposited on the wafer surface, it needs to be globally flattened again. As the only means of global flattening of wafers, Chemical Mechanical Polishing (CMP) was first invented by IBM in the 1980s. The basic principle is to use the combined effects of chemical reactions and mechanical grinding to achieve global flattening. Specifically, the wafer is fixed to the polishing head, inverted on the polishing pad, and moves relative to the polishing pad; at the same time, the polishing slurry is continuously injected into the wafer and the polishing pad, and is flattened on the polishing pad under the centrifugal force of the wafer rotation, so as to remove the material on the wafer surface by chemical reaction and mechanical grinding: first, the nanoparticles in the polishing slurry contact the wafer and react chemically to form a softened layer on the wafer surface; then, it acts mechanically on the wafer surface to remove the softened layer on the wafer surface. This process is repeated to achieve global flatness.
[0003] Silicon has a moderate bandgap and stable physical and chemical properties. It is very suitable for changing its electrical properties by introducing other atoms for doping, or depositing metals to form wires without chemically reacting with the newly introduced atoms. Therefore, it is often used as a substrate for very large-scale integrated circuits. However, high-purity single-crystal silicon is made in the form of silicon ingots, which cannot be used directly in the manufacture of wafers. It must go through processes such as cutting, polishing, and cleaning before it can be used as a substrate. After each layer of components and circuits is deposited on the wafer surface, it also needs to be flattened before subsequent processes can be carried out. Therefore, chemical mechanical polishing is a key step in the chip manufacturing process.
[0004] Ideally, CMP will quickly obtain a scratch-free polished flat surface. However, if abrasive particles with a harderness than that of single crystal silicon are used, the polishing rate will increase, but the particles will leave scratches on the surface of the single crystal silicon due to the downward pressure and rotation of the polishing head. If abrasive particles with a harderness than that of single crystal silicon are used, the polishing rate will decrease, causing the throughput of the CMP process to decrease.
[0005] The hardness of single crystal silicon is medium (Mohs hardness 6.5), and global flattening has strict requirements on the number and size of scratches on the silicon wafer surface; at the same time, considering that the hardness of amorphous silicon dioxide is softer than that of single crystal silicon (Mohs hardness 5.5), the scratches formed on the silicon wafer surface during the CMP process can be well controlled. At the same time, the hydroxyl groups on the surface of silica nanoparticles play a role in chemical reaction during the CMP process, accelerating the rate of removing substances from the silicon wafer surface, reducing the time required for the CMP process, and saving costs. Therefore, it is generally recognized in the industry that silica nanoparticle colloids are used as CMP slurry for silicon wafers.
[0006] Silica nanoparticles can be made by reacting silicon chloride gas with water vapor (gaseous silicon oxide), or by reacting organic silane with ion exchange resin (ion exchange silicon oxide), or by silane hydrolysis (hydrolyzed silicon oxide). The particle size distribution of gaseous silicon oxide is wide and the shape is uneven, which will cause a lot of scratches when used in CMP; the particle exchange method can obtain silicon oxide particles with narrow particle size distribution and uniform shape, but its production process is time-consuming and difficult to control; therefore, the silica nanoparticles obtained by silane hydrolysis are used as CMP abrasive particles;
[0007] Various metal ions, such as Na + , K + These ions will diffuse into the silicon lattice, change the bandgap width of the material, and cause abnormal leakage or even short circuit. If the influence of these metal ions cannot be eliminated during the CMP process of the wafer, the chip performance will be affected at best, forcing the chip to be downgraded or scrapped at worst. At the same time, metal ions will also adhere to the surface of the silicon wafer, causing trouble in the cleaning process after polishing. Summary of the invention
[0008] This patent application reduces the probability of metal contamination during the CMP process by completely eliminating any preparation method that may introduce metal ions to contaminate the CMP slurry, thereby alleviating the problems of product leakage and short circuit and improving the product yield. At the same time, it also improves the polishing effect, that is, it increases the material removal rate (Material Remote Ratio, MRR) and reduces the surface roughness (Ra) of the wafer. It is of great significance to prepare the transportation pipeline and equipment materials made of polyethylene PE, polypropylene PP, polytetrafluoroethylene PTFE, soluble polytetrafluoroethylene PFA and other materials.
[0009] The purpose of the present invention is to provide a nano-oxide colloidal composite material for chemical mechanical polishing of silicon wafers and a preparation method thereof. The composite material is conducive to achieving metal residue on the silicon surface, is suitable for the chemical mechanical polishing process in the field of chip manufacturing, and achieves a higher material removal rate and fewer scratches.
[0010] According to one aspect of the present application, a method for preparing high-purity nano-colloid silica is provided, comprising the following steps:
[0011] (1) mixing water, alcohol and organic amine to obtain a mixed solution I;
[0012] (2) mixing the organosilane and the alcohol to obtain a mixed solution II;
[0013] (3) Mixing the mixed solution I and the mixed solution II, keeping warm, stirring, aging, and solvent exchange to obtain the high-purity nano silica colloidal body.
[0014] The alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, and tert-butanol;
[0015] The organic amine is selected from at least one of tetramethylammonium hydroxide, ethylamine, propylamine, diethylamine, ethanolamine, diethanolamine, triethylamine, triethanolamine, and ethylenediamine;
[0016] The organosilane is selected from at least one of tetramethoxysilane and tetraethoxysilane.
[0017] In the mixed solution I, the molar ratio of water to alcohol is 1:1-50, and the molar ratio of water to organic amine is 1:0.01-10;
[0018] In the mixed solution II, the molar ratio of the organosilane to the alcohol is 1:1 to 10;
[0019] The volume ratio of the mixed solution I to the mixed solution II is 5 to 17:1;
[0020] The mixing time of the mixed solution I and the mixed solution II is 0.01 to 24 hours, within which time range nano silicon oxide particles with a small PDI can be formed to reduce scratches on the polished surface;
[0021] The insulation temperature is 10-90°C;
[0022] The insulation time is 0.5 to 24 hours;
[0023] The stirring rate is 100-1800 rpm;
[0024] The aging temperature is 10 to 90° C.
[0025] The aging time is 2 to 24 hours.
[0026] The solvent exchange refers to adding water to the precursor solution while distilling to maintain the total molar amount unchanged.
[0027] According to another aspect of the present application, a high-purity nano silica colloid prepared by the above-mentioned preparation method is provided, wherein the high-purity nano silica colloid contains nano silica particles;
[0028] The particle size of the nano silicon oxide particles is 10 to 100 nm;
[0029] Optionally, the particle size of the nano silicon oxide particles is 40 to 90 nm;
[0030] The PDI of the nano silicon oxide particles is 0.01 to 0.3.
[0031] According to another aspect of the present application, a chemical mechanical polishing slurry is provided, which is composed of an organic acid, water, a quaternary ammonium salt, dipotassium ethylenediaminetetraacetate and the above-mentioned high-purity nano-colloid silica.
[0032] The organic acid is selected from at least one of oxalic acid, formic acid, acetic acid and citric acid;
[0033] The quaternary ammonium salt is selected from at least one of tetramethylammonium hydroxide and tetraethylammonium hydroxide.
[0034] In the chemical mechanical polishing slurry, the mass content of organic acid is 0.1-1wt%, the mass content of quaternary ammonium salt is 0.005-0.010wt%, the mass content of dipotassium ethylenediaminetetraacetate is 0.001-0.0025wt%, the mass content of high-purity nano-silica gel according to claim 5 is 1-18wt%, and the rest is water.
[0035] The pH of the chemical mechanical polishing slurry is 9 to 11;
[0036] The pH value of the chemical mechanical polishing slurry can be obtained and maintained by any suitable method. Specifically, the chemical mechanical polishing slurry may further include a pH adjuster and a pH buffer. The pH adjuster is any suitable compound for adjusting the pH, such as potassium hydroxide, ammonia or a combination thereof. The pH buffer is any suitable buffering agent or buffer pair, such as phosphates, ammonium salts, sulfonates or the like. The chemical mechanical polishing slurry may contain any amount of pH adjuster and pH buffer, as long as the amount can obtain and maintain the required pH of the polishing slurry, such as pH = 10.5; the chemical mechanical polishing slurry contains 0.01 to 0.03 wt% of a surfactant;
[0037] The surfactant is selected from at least one of a nonionic surfactant, an amphoteric surfactant, a cationic surfactant, and an anionic surfactant;
[0038] The chemical mechanical polishing slurry contains 0.002-0.01 wt % of a defoamer;
[0039] The defoamer is selected from acetylene glycol defoamer;
[0040] The chemical mechanical polishing slurry contains 0.001 to 0.003 wt % of a biocide;
[0041] The biocide is selected from isothiazolinone biocides.
[0042] The chemical mechanical polishing slurry is colloidally stable. Colloidally stable refers to the property of maintaining the suspension of particles in the liquid during the entire polishing process. When the chemical mechanical polishing slurry is placed in a measuring cylinder and left to stand for 2 hours, if the difference between the particle concentration in the lower half of the measuring cylinder (calculated as the particle mass to liquid volume) and the particle concentration in the upper half of the measuring cylinder does not exceed 1% of the particle concentration of the original chemical mechanical polishing slurry, then the chemical mechanical polishing slurry is considered to be colloidally stable;
[0043] The average particle size of the particles in the chemical mechanical polishing slurry should remain substantially unchanged throughout the service life of the chemical mechanical polishing slurry. Specifically, the particles in the chemical mechanical polishing slurry increase by less than 10% during the entire service life (e.g., 90 days or more);
[0044] All the steps and operations described above use equipment, instruments, pipes, and containers made of PP, PE, PFTE, PFA or other polymers that do not contain metal elements to prevent metal ions from entering the polishing liquid product and affecting the polishing performance of the product;
[0045] According to another aspect of the present application, a chemical mechanical polishing method for a silicon wafer is provided, using the above-mentioned chemical mechanical polishing slurry.
[0046] The beneficial effects of this application include:
[0047] 1) By eliminating possible contact with metal products or substances containing metal ions during production, transportation, and storage, the metal content of the chemical mechanical polishing slurry and the probability of possible contamination by metal ions are greatly reduced, which is conducive to improving the problem of metal ion adsorption and contamination of silicon wafers during the polishing process, avoiding affecting the electrical properties of silicon wafers, and effectively improving the yield of products;
[0048] 2) By improving the consistency of the particle size of nano-silica particles, the material removal rate MRR and surface roughness Ra of the chemical mechanical polishing process are improved, effectively reducing the production time of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a TEM image of the nano-silicon dioxide particles in Example 1 of the present application, with a scale of 100 nm;
[0050] Figure 2 These are the test results of the polishing rate of silicon wafers using the nano-silicon dioxide particle colloidal polishing material in Examples 1 and 2 of the present application and Comparative Example 1. DETAILED DESCRIPTION
[0051] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed embodiments, but should include any other known changes within the scope of the claims of the present invention.
[0052] Unless otherwise specified, the raw materials in the examples of this application were purchased from commercial sources.
[0053] The analysis method in the examples of the present application is as follows:
[0054] The CMP experiment was performed using a UMT-Tribolab polisher (Bruker Corporation, USA) and a polyurethane polishing pad (Sub400 & IC1000, Dow Electronic Materials, USA).
[0055] The particle size and particle size distribution index were tested using Malvern Zeta-sizer Nano Instrument (Nano-ZS90, Thermo Fisher Scientific, USA).
[0056] SEM test was performed using JSM-7800F.
[0057] According to the implementation mode of the present application, a method for preparing nano silica colloid is provided, characterized in that organic silane is added to the catalyst liquid during the whole process of heating, stirring, aging and solvent exchange, and is prepared using transport pipelines and equipment materials made of polyethylene PE, polypropylene PP, polytetrafluoroethylene PTFE, soluble polytetrafluoroethylene PFA and other materials. The metal ion content in the polishing slurry is reduced, the problem of metal ion adsorption and diffusion to the silicon wafer causing its electrical performance to decrease is alleviated, and the yield of the product is effectively improved. The specific implementation steps are as follows:
[0058] A silicon wafer polishing liquid comprises 2% by mass of nano silicon dioxide and the remainder is water.
[0059] Example 1
[0060] Take 20g of tetramethoxysilane and 20g of ethanol and mix them. Take 15g of tetramethylammonium hydroxide, 50ml of methanol and 50g of water in a flask. Keep warm at 40℃ and 500rpm for 1h to obtain a catalytic solution. Fully mix the mixed solution with the catalytic solution and age it for 4h to obtain a precursor sol. While maintaining the mass of the precursor sol unchanged, add water to it while distilling it until all the alcohol in the sol is evaporated to obtain nano silica colloid.
[0061] The particle size of the obtained product was analyzed by Malvern dynamic light scattering instrument, and the average particle size was 71.25 nm and the concentration index PDI was 0.024.
[0062] Figure 1 is a SEM image of the nano-silicon dioxide particles in Example 1 of the present application, with a scale of 100 nm;
[0063] Conducting chemical mechanical polishing performance tests on silicon wafers on the above materials;
[0064] A polishing liquid is prepared, wherein the mass fraction of nano silicon dioxide particles is 2%, and the balance is water and ethanolamine.
[0065] Polishing process parameters: polishing pressure 2psi, polishing time 1min, polishing liquid flow 80ml / min, polishing head speed 65rpm, polishing pad speed 60rpm.
[0066] Example 2
[0067] Take 27g of tetraethoxysilane and 27g of ethanol and mix them thoroughly. Then take 37g of triethanolamine, 50ml of ethanol and 50g of water in a flask, keep warm at 40℃ and 500rpm for 1h to obtain a catalytic solution; add the catalytic solution to the mixed solution and stir it thoroughly, then age it for 2h to obtain a precursor sol; keep the quality of the precursor sol unchanged, add water to it while distilling it until all the alcohol in the sol is evaporated, and obtain nano silica colloid.
[0068] Conducting chemical mechanical polishing performance tests on silicon wafers on the above materials;
[0069] A polishing liquid is prepared, wherein the mass fraction of nano silicon dioxide particles is 2%, and the balance is water and triethanolamine.
[0070] Polishing process parameters: polishing pressure 2psi, polishing time 1min, polishing liquid flow 80ml / min, polishing head speed 65rpm, polishing pad speed 60rpm.
[0071] Comparative Example 1
[0072] Mix 43 ml of water, 50 ml of ethanol and 14 ml of tetramethylammonium hydroxide, stir at 350 rpm for 10 min at room temperature to obtain a catalytic solution, then increase the speed to 500 rpm and maintain it;
[0073] 8 ml of TEOS was poured into the catalyst solution and sealed, and then aged for 2 hours to obtain silica sol. While maintaining the quality of the solvent unchanged, water was added while distilling until all the ethanol in the sol was evaporated to obtain nano silica colloid.
[0074] Conducting chemical mechanical polishing performance tests on silicon wafers on the above materials;
[0075] A polishing liquid is prepared, wherein the mass fraction of nano silicon dioxide particles is 2% and the balance is water.
[0076] Polishing process parameters: polishing pressure 2psi, polishing time 1min, polishing liquid flow 80ml / min, polishing head speed 65rpm, polishing pad speed 60rpm.
[0077] Figure 2 These are the test results of the polishing rate of silicon wafers using the nano-silicon dioxide particle colloidal polishing material in Examples 1 and 2 of the present application and Comparative Example 1.
[0078] By using equipment, instruments, pipelines, and containers made of metal-free PP, PE, PFTE, PFA or other polymers that do not contain metal elements, a chemical mechanical polishing slurry containing nano-silicon oxide with uniform particle size distribution is prepared by the method of hydrolysis of organic silane, a higher polishing rate is achieved in the chemical mechanical polishing process of silicon wafers, and production efficiency is improved. At the same time, the chemical mechanical polishing slurry avoids the introduction of metal ions, alleviates the problem of metal particles being adsorbed on the wafer surface or diffusing into the wafer during the polishing process to affect chip production, and effectively improves product yield.
[0079] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing high-purity nano-colloid silica, characterized in that: The following steps are involved: (1) mixing water, alcohol and organic amine to obtain a mixed solution I; (2) mixing the organosilane and the alcohol to obtain a mixed solution II; (3) Mixing the mixed solution I and the mixed solution II, keeping warm, stirring, aging, and solvent exchange to obtain the high-purity nano silica colloidal body.
2. The preparation method according to claim 1, characterized in that: The alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, and tert-butanol; The organic amine is selected from at least one of tetramethylammonium hydroxide, ethylamine, propylamine, diethylamine, ethanolamine, diethanolamine, triethylamine, triethanolamine, and ethylenediamine; The organosilane is selected from at least one of tetramethoxysilane and tetraethoxysilane.
3. The preparation method according to claim 1, characterized in that: In the mixed solution I, the molar ratio of water to alcohol is 1:1-50, and the molar ratio of water to organic amine is 1:0.01-10; In the mixed solution II, the molar ratio of the organosilane to the alcohol is 1:1 to 10; The volume ratio of the mixed solution I to the mixed solution II is 5 to 17:
1.
4. The preparation method according to claim 1, characterized in that: The insulation temperature is 10-90°C; The insulation time is 0.5 to 24 hours; The stirring rate is 100-1800 rpm; The aging temperature is 10 to 90° C. The aging time is 2 to 24 hours.
5. A high-purity nano-colloid silica prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The high-purity nano silica colloidal body contains nano silica particles; The particle size of the nano silicon oxide particles is 10 to 100 nm; Preferably, the particle size of the nano silicon oxide particles is 40 to 90 nm; The PDI of the nano silicon oxide particles is 0.01 to 0.
3.
6. A chemical mechanical polishing slurry, characterized in that: The invention is composed of organic acid, water, quaternary ammonium salt, dipotassium ethylenediaminetetraacetate and the high-purity nano silica colloid described in claim 5.
7. The chemical mechanical polishing slurry according to claim 6, characterized in that: The organic acid is selected from at least one of oxalic acid, formic acid, acetic acid and citric acid; The quaternary ammonium salt is selected from at least one of tetramethylammonium hydroxide and tetraethylammonium hydroxide.
8. The chemical mechanical polishing slurry according to claim 6, characterized in that: In the chemical mechanical polishing slurry, the mass content of organic acid is 0.1-1wt%, the mass content of quaternary ammonium salt is 0.005-0.010wt%, the mass content of dipotassium ethylenediaminetetraacetate is 0.001-0.0025wt%, the mass content of high-purity nano-silica gel according to claim 5 is 1-18wt%, and the rest is water.
9. The chemical mechanical polishing slurry according to claim 6, characterized in that: The pH of the chemical mechanical polishing slurry is 9 to 11; The chemical mechanical polishing slurry contains 0.01 to 0.03 wt % of a surfactant; The surfactant is selected from at least one of a nonionic surfactant, an amphoteric surfactant, a cationic surfactant, and an anionic surfactant; The chemical mechanical polishing slurry contains 0.002-0.01 wt % of a defoamer; The defoamer is selected from acetylene glycol defoamer; The chemical mechanical polishing slurry contains 0.001 to 0.003 wt % of a biocide; The biocide is selected from isothiazolinone biocides.
10. A chemical mechanical polishing method for silicon wafers, characterized in that: The chemical mechanical polishing slurry according to any one of claims 6 to 9 is used.